Cutaneous plasmacytosis: a clinicopathologic study of 12 cases in Taiwan revealing heterogeneous underlying causes - Lu, Pei-Hsuan; Shih, Lee-Yun; Yang, Chih-Hsun; Kuo, Tseng-tong (International journal of dermatology, 2015)
Background Cutaneous plasmacytosis is clinically characterized by multiple pigmented papules and plaques that occur mainly on the trunk and many plasma cells in the lesional skin. Most of the cases reported have occurred in Japan. Whether cutaneous plasmacytosis is a unique reactive disease or a neoplastic condition has not been established. Methods We collected 12 cases fulfilling the criteria for a diagnosis of cutaneous plasmacytosis at our institution from 2001 to 2013. We analyzed clinicopathologic features and performed immunohistochemical and immunoglobulin gene rearrangement studies. Results All 12 patients presented with characteristic cutaneous lesions mainly on the trunk and proximal extremities. Many plasma cells were observed in the lesional skin, and the basal layer was hyperpigmented. Four patients had numerous plasma cells in lymph nodes, and one patient also had increased plasma cells in bone marrow. One patient fulfilled the criteria for immunoglobulin G4 (IgG4)‐related lymphadenopathy. Elevated serum IgG and IgG4 concentrations were found in seven patients. Monoclonal immunoglobulin gene rearrangements were detected in four patients. The median duration of follow‐up was four years. One patient was lost from follow‐up. Partial remission of the cutaneous lesions was observed in five patients, and progressive disease was noted in five patients. One patient died of respiratory failure. Conclusions Our study suggests that the so‐called “cutaneous plasmacytosis” has heterogeneous underlying causes with or without systemic involvement and may be associated with clonal immunoglobulin gene rearrangements and IgG4‐related lymphadenopathy. No effective treatment is available for this condition.